On the Cu(III)/Cu(II) Redox Chemistry of Cu-Peptide Complexes to Assist Catalyst Design. Issue 2 (4th March 2017) - Pap, József S.; Szyrwiel, Łukasz
Graphical Abstract: Abstract : The versatility of copper-peptide complexes offers several options for adjusting their pH-dependent speciation, stability, and redox properties. In context, their bio-inspired and prospective catalytic applications receive distinguished attention. There are a number of Cu-catalysts (including some Cu-peptides) that utilize Cu(III) as part of the catalytic cycle and, in those cases, this oxidation state has been thoroughly characterized. However, the Cu(III) state for peptide complexes in general has been less studied. Compared to the sophisticated characterization of the Cu(II) equilibrium species, the precise evaluation of their Cu(III)/Cu(II) redox processes is scarce. Considering their potential catalytic applications, understanding their redox behavior would be essential. In this brief comment, a methodology and its background are discussed that aim to highlight relations between the Cu(III)/Cu(II) formal potentials, the difference in the association constants (stability) of the oxidized and reduced forms, and the ligand constitution for a number of mononuclear copper-peptide complexes.